Evaluation of academic engagement among faculty of two Mexican and Colombian Universities. (2018)
In the last two decades, the New Public Gestion model has modified the objectives of the Universitarian Education. However, faculty has been able to face these new psychosocial consequences of their jobs, using among others the Work Engagement concept